A study on SME software development background and risk assessment implementation in Malaysia - Sharif, A.M. (2013)
In Malaysia, majority of the Small and Medium Enterprises are from services sector including Information and Communication Technology and more than two-third of the companies are microenterprises. Nearly one-third of these companies are located in Klang Valley, Johor and Perak. Our research focus is to study the implementation of risk assessment and usage of tools to identify and analyze risks in projects for those companies in the services sector who does software development projects. Also, in terms of enterprise and their staff, to examine their experience of risk and knowledge of working with project management related software development projects. Moreover, the research examines the usability of risk assessment tools in these companies and the reasons that may cause of not taking any advantage of the existing tools. Finally, the researchers enlighten some gaps in the field that needs more focus with further directions. Â© IDOSI Publications, 2013.